2023
DOI: 10.3389/fncel.2023.1125109
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of the blood-brain barrier by COVID-19 and its implication in the permeation of drugs into the brain

Abstract: Diverse neurological symptoms have been reported in patients with SARS-CoV-2 disease (COVID-19), including stroke, ataxia, meningitis, encephalitis, and cognitive impairment. These alterations can cause serious sequelae or death and are associated with the entry of SARS-CoV-2 into the Central Nervous System (CNS). This mini-review discusses the main proposed mechanisms by which SARS-CoV-2 interacts with the blood-brain barrier (BBB) and its involvement in the passage of drugs into the CNS. We performed a searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 48 publications
1
17
0
1
Order By: Relevance
“…Sepsis may induce disruption of the blood–brain barrier (BBB) and may also cause cerebral hypoperfusion [ 5 ]. Similar mechanisms have been proposed in COVID-19 [ 6 , 7 ]. SARS-CoV-2 infection has been associated with neurological complications [ 8 ], and the severity of COVID-19 seems to be an important determinant [ 9 ].…”
Section: Introductionsupporting
confidence: 69%
“…Sepsis may induce disruption of the blood–brain barrier (BBB) and may also cause cerebral hypoperfusion [ 5 ]. Similar mechanisms have been proposed in COVID-19 [ 6 , 7 ]. SARS-CoV-2 infection has been associated with neurological complications [ 8 ], and the severity of COVID-19 seems to be an important determinant [ 9 ].…”
Section: Introductionsupporting
confidence: 69%
“…Several studies reported signs of neuroinflammation in tissue from COVID-19 patients (reviewed by (Almutairi et al, 2021; Brown et al, 2023; Gonçalves de Andrade et al, 2021; Hernández-Parra et al, 2023; Iadecola et al, 2020; Natale, Lukens, & Petri, 2022; Tremblay et al, 2020; Vanderheiden & Klein, 2022; A. C. Yang et al, 2021)). SARS-CoV-2 not only infects the respiratory tract but also other organs, including the brain and its cerebrovasculature (Y.…”
Section: Discussionmentioning
confidence: 99%
“…Among the cytokines are interleukin 2R, interleukin 6, interleukin 8, tumor necrosis factor (TNF, also known as TNF-alpha) and, interestingly, also the anti-inflammatory interleukin-10 (Devlin & Gombolay, 2023; Liu et al, 2020). Macrophages and lymphocytes penetrate the blood-brain barrier, activate microglial cells and astrocytes and finally determine neuroinflammation (Almutairi et al, 2021; Brown et al, 2023; Gonçalves de Andrade et al, 2021; Hernández-Parra et al, 2023; Iadecola et al, 2020; Tremblay et al, 2020; Vanderheiden & Klein, 2022). In our study, both microglial cells and astrocytes showed an activated phenotype in COVID-19 patients, confirming neuroinflammation.…”
Section: Discussionmentioning
confidence: 99%
“…However, in scenarios where the BBB is compromised, neutrophils infiltrate and NETs are often visualized in brain tissue where they contribute towards ongoing neuroinflammation ( 260 , 261 ). Recent studies proposed that COVID-19 facilitates BBB disruption by increasing the expression of matrix metalloproteinase-9 (MMP-9) which leads to basement membrane degradation ( 262 , 263 ). The levels of NETs in the brain have been directly related to the degree of neuroinflammation in model organisms of Alzheimer’s disease, meningitis, ischemic stroke, and traumatic brain injury ( 264 ).…”
Section: Neutrophil Extracellular Traps In Long Covidmentioning
confidence: 99%